Infectious complications after hematopoietic stem cell transplantation for primary immunodeficiency in children: A multicenter nationwide study. Issue 5 (6th April 2020) - Zając‐Spychała, Olga; Zaucha‐Prażmo, Agnieszka; Zawitkowska, Joanna; Wachowiak, Jacek; Kowalczyk, Jerzy R.; Frączkiewicz, Jowita; Salamonowicz, Malgorzata; Kałwak, Krzysztof; Gorczyńska, Ewa; Chybicka, Alicja; Czyżewski, Krzysztof; Dziedzic, Magdalena; et al.
Abstract: Purpose: The aim of this nationwide study was to evaluate the characteristics of bacterial infections (BI), invasive fungal disease (IFD), and viral infections (VI) in pediatric patients with PID after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Patients and methods: In total, 114 HSCT recipients were enrolled into the study. At least one infectious complication (IC) was diagnosed in 60 (52.6%) patients aged 0.1‐17.7 years, that is, 59.5% with SCID and 49.4% with non‐SCID. Results: Among 60 HSCT recipients diagnosed with at least one IC, 188 episodes of infectious complications (EIC) were recorded, that is, 46.8% of BI, 41.5% of VI, and 11.7% of proven/probable IFD. According to PID and HSCT donor type, the incidence of EIC was comparable ( P  = .679). The localization of infections differed significantly due to PID type ( P  = .002). After each HSCT donor type, the most common site of infection was GI. Overall, BI caused by Gram‐positive strains (59.1%) were prevalent, especially Staphylococcaceae . The multidrug‐resistant (MDR) pathogens were diagnosed in 52.3%, especially ESBL +  Enterobacteriaceae . The profile of VI was comparable for SCID and non‐SCID patients ( P  = .839). The incidence of IFD was comparable for each PID and HSCT donor type. Survival after infection was 91.5% and was comparable for PID and HSCT donor type. Conclusions: The rate of patients diagnosed with IC among pediatric PID‐HSCT recipients did not depend on PID type, but rather on HSCT donor type. The localization of IC depended on PID and HSCT donor type. Within bacterial infections, predominated Gram‐positive strains and the MDR pathogens were responsible for more than half of EIC.